2020
DOI: 10.1142/s0217984920501316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhomogeneous laser field in time and space on the generation of broad spectral continuum and ultrashort attosecond pulse

Abstract: The inhomogeneous effects of laser field in time and space on the generations of high-order harmonic spectra and attosecond pulses from He atom have been investigated with the assistance of the frequency-chirping technique and the metallic nanostructure. We find that in different combinations of chirps and spatial inhomogeneous effects, not only can the harmonic cutoff be extended, but the single harmonic emission peak (HEP) can also be selected to contribute to the spectral continuum. In detail, with the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…More recently, generation of a single attosecond pulse with the help of the asymmetric polarization-gating technique was analyzed [60], as well as with three-color electric fields [61]. Also, in [62] the influence of the time and space inhomogeneities of the laser field on the HHG spectra and the attosecond pulses was investigated, while in [63] a method to produce circularly polarized attosecond pulses with tunable helicity from a CO molecule was proposed. Finally, it was shown that the ellipticity of attosecond pulses can be controlled in plasmonic-enhanced counter-rotating bicircular fields [64].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, generation of a single attosecond pulse with the help of the asymmetric polarization-gating technique was analyzed [60], as well as with three-color electric fields [61]. Also, in [62] the influence of the time and space inhomogeneities of the laser field on the HHG spectra and the attosecond pulses was investigated, while in [63] a method to produce circularly polarized attosecond pulses with tunable helicity from a CO molecule was proposed. Finally, it was shown that the ellipticity of attosecond pulses can be controlled in plasmonic-enhanced counter-rotating bicircular fields [64].…”
Section: Introductionmentioning
confidence: 99%